Some Details on Tariff Policy (Quarterly Journal of Economics, 1941)
Some Details on Tariff Policy Get access The Quarterly Journal of Economics, Volume 56, Issue 1_Part_2, November 1941, Pages 154–157, https://doi.org/10.1093/qje/56.1_Part_2.154 Published: 01 November 1941